Analysis of the Law Enforcement on Illegal Mining in the Rehabilitation Area of Gunung Menumbing Grand Forest Park, West Bangka Regency - Angel, Angely Priatna Putri; Tamrin, Husni (Journal of Law, Politic and Humanities, 2025)
Illegal tin sand mining in the rehabilitation area of Gunung Menumbing Forest Park (Tahura) in West Bangka Regency poses a serious threat to the ecosystem and the conservation functions of the area. However, the illegal tin sand mining occurs in the rehabilitation block of Gunung Menumbing Forest Park, a block that had already suffered damage due to natural factors. This study aims to analyze the implementation of criminal law against illegal mining activities and the effectiveness of law enforcement. The research adopts a socio-legal approach with an empirical juridical method, collecting data through document studies, field observations, and interviews with stakeholders in the area. The findings indicate that although legal regulations such as Law No. 41 of 1999 on Forestry and Law No. 32 of 2009 on Environmental Protection and Management are sufficiently comprehensive, their implementation still faces various obstacles. The hindering factors include limited personnel and surveillance technology, as well as the community's economic dependence on illegal mining. From 2023 to 2024, six criminal cases and seven suspects involved in illegal mining activities have been recorded in the rehabilitation block of Gunung Menumbing Forest Park. The study concludes that law enforcement has been ineffective due to weak legal structures and a social culture that is permissive toward environmental violations. Recommended actions include strengthening the capacity of law enforcement agencies, improving inter-agency coordination, and implementing community empowerment programs to create sustainable economic alternatives